Ticari bankalarda kredi fiyatlandırma politikası - Yüksel, Aslı (My University, 2000)
Ö Z E T Türk bankacılığında ürün fiyatlandırması, literatürde çok işlenmemiştir. Çünkü yakın geçmişe kadar Türkiye' de özellikle bankacılıkta fiyatlara resmî müdahale geniş kapsamlıydı. Çalışmanın ilk bölümlerinde; genel kavramların açıklanmasından sonra kredi fiyatlandırma yöntem ve politikaları ele alınmıştır. Bu bağlamda kredi veriliş işlem ve aşamaları, bankacılıkta fiyatlandırma politikası, banka işletmesinde ürünün ve fiyatının özellikleri, fiyata müşterinin olası tepkileri ve fiyat belirleme biçimleri ve fiyat modelleri, asgari fiyat sınırının önemi ve saptanması ele alınmış; daha sonra fiyat esnekliğinin fiyat belirlemedeki rolü araştırılmıştır. Sonraki bölümde müşteri verimliliği ve gelirleri hesabına değinilmiş; bu bağlamda kredi maliyeti açısından pazar faizi yönteminin temel alınmasının anlam ve önemine yer verilmiş, başlıca getiri kalemleri tek tek incelenmiştir. Daha sonraki bölümde de kredi fiyatının bileşimi ve banka açısından kredi maliyeti öğeleri ayrı ayrı incelenmiştir. Bunlar arasında işletme giderleri, kredi riski maliyeti,

sermaye maliyeti ve yasal, elde hazır değer bulundurma zorunluluğundan doğan ek maliyet konuları incelenmiştir. Daha sonraki bölümlerde yasal anlamda faiz türleri ve Türkiye' deki temel kuralları incelenmiştir. Bu arada; maliyet öğesi olarak genellikle ihmal edilen ve fakat finans sektörü işletmeleri için beklenmedik dönemlerde yaşam sorununa dönüşebilen kredi risk maliyeti temeli üzerine kredi riski ölçülmesi, önlemleri, risk dağıtım politikaları ile küresel bankacılığın yeni bir konusu kredi finansal türev ürünleri incelenmiştir. Son bölümlerde yeni bankacılık çağının güncel konuları arasına giren reform konu ve alanları (bu arada Lean Banking ve Business Reengineering gibi) sorunlar ele alınmış, giderlere egemen olma zorunluluğunun ortaya çıkardığı yeni rekabet stratejileri gereklerine değinilmiştir. Son bölümde de cevap alınmasını kolaylaştırmak amacıyla mümkün olduğunca kısa tutulmağa çalışılan bir anketle Türk bankacılığında fiyatlandırma konusunun ele alınış biçimi araştırılmış ve değerlendirilmiştir. CREDIT PRICING POLICY IN COMMERCIAL BANKS Product pricing is not a subject to be discussed too often in literature. Recent history of application of tariff system in Turkey is a reason of this. In the banking sector, the relation between cost and prices show differences according to other business enterprises. The main reason is that the banks create money. But, this power which are in the hands of the banks, has been under the control of money authority for a long time. Date of the liberation of the prices in credit and deposit transactions is not too old. Therefore, it has been a necessity to make such a through study of the pricing subject in the banking, which has gained importance, as a result of the global financing. The financial crisis which has been experienced in the economy and effecting the banking sector lately, has also been an indicator of lack of control, management, and equity capital in Turkish banking. The thesis consists of 7 chapters. There are basic concepts in the first chapter. Afterwards, it is defined how the crediting stages are realised and what are the points, known or unknown by customer during the giving of the credit decisions. As a summary of all these, following stages will be monitored during the giving of credit decisions: 1. Consultation Stage · Calculation of capital requirement. ( How much money do ı need? · Selection of the financing type ( Which financial sources will be used to meet the requirement? · Developing of an optimum financial package. ( Mixed financing) · Consultation Interview (Credit meeting) 2. Application Stage · Compiling of documents (Balance sheet, gain and loss statement. Commercial registration and etc.) · Filling up of the application forms, 3. Preparation Stage · Evaluation and analyse of balance sheet, · Evaluation of relations with the banks and compiling of commercial data, · Cost analyse and casting of total depth 3. Evaluating Stage · Evaluation of the suitability to the individual credit · To determine the ability of crediting from the economical direction. · Evaluation of guarantees (economic value and legal consistency) · Calculation of risk division, · Determining and reporting of the opinion related to the credit application, 5.Decision Stage · Credit Service (Verbal/ Written) · Consulting and interview ( Within the frame of the credit committee) · Taking of the credit decision by authorised organ 6. Management Stage · Writing of credit forms and contracts, · Making of private contracts related to the credit guarantees, · Formal inspection of the credit correspondence · Compiling of the customer's circular of signatures, · Getting the agreed guarantees. · Arranging the files and opening the accounts. 7.Controlling stage · Controlling the credit file from the point formal point of the view · Controlling the guarantees · To contact with respective departments when finding out the Deficiencies. 8. Payment Stage · If available opening the credit through software, · Informing the customer availability, opening, and authorisation of the credit 9. Observation (Auditing) stage · Auditing the credit user's economical and legal status · Auditing the credit conditions · Auditing the guarantees, · Auditing the purpose of the credit using · Monitoring the progress of the account constantly (Exceed of the credit limits, warnings, and notices etc.) 10. Terminating Stage · Evaluation of account balances · Calculations of period of times and file closing. · Closing the file (Closing the account) · Releasing the guarantees. · Informing the customer from the situation. Different departments in the bank undertake the performances at each of these stages. ( Credit Department, Intelligence Department, Operation, credit, control and correspondence departments, legal works consultant services and etc.) After evaluation of credit applications, at the same place also pricing policy of the bank takes place. The aim of the price policy is to ensure necessary circumstances for creating updated price movement area According to this, the target of price policies for certain banking products are : · meeting the cost of the product · providing a suitable income and · to constitute a price policy to compete in the market against the products of rivals. · There are two choices for the bank here to determine the price. In order to hold on against competition : Either should select the service leadership if trusting his institutional identity or image and has a well known name in the market , or cost initiation for standard mass products. Most general methods used in determining the price: Pricing based on the cost : A certain amount to cover the credit is added on the cost of product units. In this case, pricing starts from the product which will be presented, then price of the product and up and down limitations of this price are determined. That means, market's properties are less considered in pricing based on cost. This pricing method does not create a problem , if the bank has a monopoly and the market is not flexible price wise. But, if the cost of the bank is over the market of rival banks, the it becomes impossible to sell the product, or can be sold at a loss. Actually, the situation in west banking which is observed nowadays as it is mentioned above But, if the pricing is based towards to the market, a function of price is added to the relation of cost and price. The measurement here, what should be the price of the product, which can be accepted by certain customer segment. The price can be formed in accordance with the target price and the target cost. The benefit of this method is to create a better price by calculating of observed price flexibility. But this price determined by the market might not always provide the bank's target optimisation or to bring it to the maximum level. The implementation of pricing based towards to the market policy has also its own difficulties because of data compiling difficulties in application. One of the ways to avoid these problems is to monitor the rival bank's price methods. In this method, the rivals' costs are adapted and rival bank prices are taken over. And the rival's prices are used as target data within the frame of Target Costing. Another name of this method, using rival banks' costs as a basis for their own optimisation of the cost structure is Benchmarking. An effective method of determining the price, maybe is the combination of the orientation of these three. The sensitivities of the demand owners against the price are taken into the consideration as well as the bank's internal expenditures within this frame. This method, gives the bank the opportunity to determine the minimum limitation of the price and in the other hand to find out the maximum price which can be asked from the market. Bottom limitation with short periods of the price can also be found out by taking into the consideration of the cost of limitations. But in the long term, the determined price should also meet the bank margin and profit as well as cost of the credit. Actually, the traditional banking pricing method is the percentage model. In this model, the price of the product is measured by the percentage of the amount of the credit or envisaged service. If the bank wishes to form a price for all services separately it might prefer to use , a method, by pricing each service or using certain basic products together to form a wholesale fee or for services require personal consultation services such as (portfolio management, legal and tax advice) a fee based on performance or time , to use a mixture of all of them. In reviewing the costs applications of profit center can be used. Information related to the customers can be obtained from here. In the third chapter the risks which play an important role in crediting is explained. In evaluating the credits, subjective and objective methods are used as Risk Measurement Technologies. Subjective Methods: (Traditional methods) The measuring of the credit risk mostly is up to the initiation, experience and ability of personal perception of the customer representative. If the period of time of the relation, between credit customer and customer representative gets longer, the ability of the perception of early warning signals of the customer representative is decreased. Apart from this, customer representative might prefer to ignore some signals with an appetite for success. The benefit of this method is to shorten the time for the decision making, but, the mechanism for proof and control is very difficult for operating. This method is based on reviewing only the character of the 5 C criterions of crediting. Character shows the payment habit and honesty of the customer. Objective Methods : That means the use of the modern technologies in credit opening operations. It consists of the signals of rating, scoring and early warning mainly. It also calculates other C es apart from the character ; Capacity, Collateral, Conditions, Control. Benefit : It is a transparent method which can also be proved. Disadvantage : Customer quality is not taken into the consideration. The measurement costs of the credits are too high in the first stages of the credit relations therefore banking system prefers this method nowadays. The ideal system is to find out a common way of evaluation of subjective and objective methods. Therefore Swiss Banking uses a method called CRM IT (Credit and Risk Management Information Technology ) consist of a computer system and early warning system. Credit demands are analysed in this system , CRM IT , and reaches to the permission stage. There are two branches of the system: 1) Evaluation of the quality of the customer relation: Customer's quality ( Training, management, payment habits) data and intelligence results as well as investment project and strategies are evaluated and scored. 2) Evaluation of quantitative data : reviewing of data of balance sheets for the last three years, account information, and other data apart from the bank, and dynamic analyses are done for sectors separately. CRM-IT makes a recommendation under the light of the qualitative and quantitative data. But the last decision is again within the authority of the customer representative. Early Warning System : It is a system mostly used in inspection of the credits. It is a process which is monitored with the computer system after opening the credit and for the controlling of the risk status. All customers are monitored and inter activated with each other. There are various methods in limiting the credit risks. The latest of then is Credit derivative products. Financial credit derivative instruments : It is an instrument allows the one of the parties to transfer the risk of the credit of the active, to someone else against payment of a premium, and out of balance sheet. In this manner, the risk taker, without obligation of buying, undertakes the risk of the credit of the referred active. The scope and amount of the payment which are contained in the financial credit derivative instruments, depend on the realisation of a risk in the credit transaction that means the measurement of the credit return risk or change in credit rating. Financial product active can be consist of one or more creditors' names or a certain index. Payment obligation can be decided also as cash, active instrument based in the transaction or in the form of physical portfolio delivery. Benefits of the Credit Derivatives: 1. The banks can lower their risks. 2. Avoiding the disadvantages of the transactions in the money market, such as operation costs, and taxes, while credit risk is being eliminated. 3. It is a common place where the investors and crediting organisations are displayed. 4. A place where the banks can correct their risk yield profiles. 5. With Credit derative products, assets remain in balance sheet as it is, only, the risk is sold. Disadvantages: Available data is insufficient. Market is not transparent. There fore the development of the market is very slow. It is hoped that in the long term , the credit derivative products will make the credit risks more transparent and bring a more effective management over the credit risks. There are also two parties in credit derivative products as well as in other financial derivative products. Buyer of the Risk and seller of the risk. The selling party sells the risk resulting from the credit (That can also be called Bonite risk) against a premium to the buyer of the risk. Buyer of the Risk buys the so called bonite risk without base instrument, that means buying without taking over the credit in fact. In that case, it is understood that the risk buyer undertakes the negative results which might be aroused from the transaction. A direction of goods or payment movement arousing from the implementation of a credit instrument, is tied up in a contract between the risk buyer and seller. Basic chapters of such an agreement, are first concretization of payment status, credit margins, and credit ratings. It brings out to the banks an obligation of controlling their costs as a result of global financing apart from the decreasing the effects of the credit risks. The details of this subject are explained in chapter 5. Global financing is sped up due to revelation of deregulation, technological developments, importance of the diversified portfolios in risk management and futures market. Along with the benefits of global financing which presents of finding easy credit possibilities in better conditions, and lowering the cost of loans, it may also bring along a serial of negative effects such as moving in herds to the developing countries' economies, and out also in herds, causing financial crisis, and infecting these crises to other markets, as a result of irregularity which makes the controlling almost impossible. Financial Sector as a result of the Global financing. They have to reduce their costs, without making a concession from their quality, focus on their customers. They will succeed these through a smooth active and passive management and applying a structural reorganisation. The priority is focusing on the customers. It is necessary to determine product prices, services and presentation for different customer groups. According to the principle of centrifugal, less hierarchy and more authorities are essential. Scoring and early warning systems should be in the hands of the lower level managers. Progression according to the Business Reengineering: should be divided to parts asper the characteristics of routine being. It is called triage). For example, while giving the decisions of basic credits by computer software, middle level credit decisions can be given by dealers or specialists. This way organising and specialisation might function together. In and outside customer satisfaction should be the main purpose. According to a research of City Bank, customer satisfaction starts dropping after the 5th minute. As a result of global financing, it is essential that the banks should give the importance to the joining to get stronger. The reason for this necessity is ; To enlarge the market share against rivals, To provide and using of the narrowing sources, There is a criterion problem in banking. Bigness is important for the customers. The bigness is important to reach new equity capitals, balancing the risk, and diversifying the products. The reducing of the expenditures, the rising of the profitability, the increasing the of market place are realised by benefiting from the synergy potential. But it appears that results of the joining do not reflect the expected effects. It is mostly because of the managers who approaches the joining in the direction of their egos, ignoring the planning and activities, additional costs and hostile purchasing. (Such as co ordination of human resources, risk planning and inspection) Outcome and evaluation: · In the world banking, electronic based products and systems are spreading quickly. As a follower of this matter, respective investments should be made without any delay, since they will be reducing the costs in long term, despite of the financial burden at the beginning. In this manner, distribution channels should be enlarged. In today's banking, Product based intensifying has left its place to customer focused intensifying. · As a result of the global financing, competition has reached its highest level between the banks, the heaviness of competition weights on the price policy. In this respect, the banks should take immediate precautions to keep the costs under control. · As another problem of global banking today, the banks should stop the subvention of the services which are causing losses with the profiting ones, and they should be specialised in the subjects in which they are superior. The bank prices should be based on the costs and the banks should focus following matters and determine where they stand: Who are the target customers? Where are they standing in the developing market? What are their superiority from rivals? The banks should show their superiority and they should give up from the idea of being present in each subject and field and leave the certain matters to their specialists. In the meantime, according to the new rules of Bank für Internationalen Zahlugsausgleich (BIZ) which took rather progressive steps about the subject of the international equity capital inspection, the banks will not be contended with a certain ratio of equity capital for the bank credits, in the opposite, they will direct their safety margins to an expensive equity capital form which suits to each debtor's bonite in the future. Lower risks will be met by less equity capital, and bad debtors will have to use more expensive credits. Therefore, the real risks will be more transparent. Because of this, credits of some customers will be more expensive. Therefore, it will be the job of the debtor, increasing his bonite in order to reduce his credit cost. · The risk estimation should be the first factor in determining the right price, therefore, it seems benefiting from the methods of diversifying and limiting the risks in a certain ratio is inevitable. In related to this, the studies with credit derivative instruments should be started. · The banks, should aim to reduce the cost and time in analysing of evaluation of credit risks, by either should enlarge the data bases or transfer these type of analyses to rating or scoring organisations. · The people when they are choosing their bank they will investigate the ratio of price/ service very carefully, and the service quality and reliability of the bank will be an important factor in this respect. · There is an excessive capacity problem in banking. Branch banking will transfer its place to other alternative distribution channels gradually. · Banks also have to reduce their operation costs. Therefore some services will be delegated to outside instead of employing people in the bank. (Such as human resources, legal works, catering, and public relations) · The time during the crediting should also be taken into account while calculating the bank's expenditures. The shortening of this period should be taken into the consideration to reduce the costs. But, in practise, it is tried to meet the losses of small credits with the profit of a few big credits. · Credit inspecting expenditures are not as high as the crediting costs, but it increases when the credit period gets longer. This effects to the costs. Inspection is important. At this point, early warning signals should come in, and a group from working personnel should be delegated. · The measurement and distribution of the credit is a big problem. The banks have to organise risk committees very seriously and should consider the matter in higher levels anymore. Apart from this, there is also a remarkable increase in the variety of the risks. Along with credit, liquidity, equity capital, and market risks, image loosing risk, and moral risks have been added. In analysing of credits, subjective and objective risk evaluations should be used together and should form a data base, like CRM IT. These analyses are big cost factors for the banks. Therefore it is much more benefiting for the banks to work with rating and scoring institutions. · There is a bigness problem in banking . Financial sector in Turkey is very weak. The amount of the actives of all the banks is equal to the amount of one middle sized bank in Europe. It seems the joining of the banks is inevitable at this situation. · Also, the bigness of the banks can not only be measured with the amount of their active or number of the personnel. As a result of joining, market share, new customer portfolios, criterion and diversification effects, largeness of the movement space in deciding in the price policy, transition to the alternative distribution channels, ability for practising the new technologies, personnel training, ability to renewing period, will be improved by synergy. · The obstacle in front of the joining of the banks in Turkey is that enough rivalry atmosphere has not yet been created. The unnecessary assurance of the savings, prevents entries and exits to the banking sector. The existing of unprofitable banks which are only standing by the precautions limiting the competition, prevent the sector to renew itself. These are damaging the market conditions. · The personnel in the banks should have an on time and better training to be able to operate in international markets, lacks of communications in the system should be eliminated. · The banks should make their prices more transparent to enable their customers to decide consciously. (Specially, in Turkish banking the commission subjects and amounts are showing big differences). In this respect, the banks should form cataloques where they can present and fix prices for hundreds of products like GRAPA Customer Relations and Profitability Analyses application in Switzerland. · The banks which are rising the quality of their personnel by investing to people, will be able to catch the customers who are constantly expecting good service. Taking into the consideration that individual banking is expected to be the focus in the years of 2000, it becomes an obligation. · The true customers of a bank will not consider changing their bank despite of small price differences. Therefore, the banks which ensure reliability, quality and speed will be in a very advantageous position.
Keywords: Banka kredileri; BANKACILIK-KREDİ DEĞERLEME; KREDİLER